Use of the project-based learning methodology to improve the writing english language skills. - Pesantez Suarez, Magdalena Lisseth (Machala: Universidad Técnica de Machala, 2025)
This research aimed to improve the English writing skills of tenth-grade students of (GBE), room ‘‘D’’ at ‘‘N.A’’ Educational Institution, through the implementation of a class system based on the Project-Based Learning (PBL) methodology. The study followed a quantitative approach with a pre-experimental design applied to a single group. To measure the impact of the intervention, both theoretical and empirical methods were used, including observation and pedagogical tests (pre-test and post-test). The findings revealed notable improvements in the writing components assessed: content, grammar, vocabulary, and organization. Initially, most students performed at low levels, reflecting serious deficiencies in written production. After applying the class system, students demonstrated improved sentence construction, vocabulary usage, grammatical accuracy, and text coherence. The intervention was carried out over two weeks, with a total of four class sessions focused on developing writing through real-life and meaningful tasks. Students worked in small groups to create written projects, such as emails, allowing them to apply language structures in authentic communicative contexts. The activities incorporated review of grammar tenses, vocabulary building, and organization of ideas using logical connectors. In addition, the constant feedback from peers and the teacher throughout the process helped students to reflect on and enhance their own writing. The study concludes that PBL encouraged active, meaningful, and contextualized learning, effectively enhancing students’ writing skills in English. It also fostered collaboration, critical thinking, and autonomy in the classroom. This research supports the use of PBL as a powerful teaching strategy in traditional educational settings.
El presente estudio tuvo como objetivo mejorar la habilidad escrita en ingles de los estudiantes de décimo año de Educación General Básica de la Institución Educativa ‘‘N.A’’ mediante la implementación de un sistema de clases basado en la metodología de Aprendizaje Basado en Proyectos (ABP). El enfoque fue cuantitativo, con un diseño pre-experimental aplicado a una sola muestra. Para evaluar los efectos de la intervención, se emplearon métodos teóricos y empíricos, tales como observación y pruebas pedagógicas (pre-test y post-test). Los resultados obtenidos mostraron mejoras significativas en las dimensiones evaluados de la escritura: contenido, gramática, vocabulario y organización. Antes de la intervención, la mayoría de los estudiantes se encontraban en niveles bajos de desempeño, evidenciando deficiencias en la producción escrita. Posteriormente, tras la implementación del sistema de clases, se observó un avance general en la redacción de textos, el uso adecuado y amplio del vocabulario, el uso de estructuras gramaticales y los textos con coherencia. La intervención se desarrollo durante dos semanas, con un total de cuatro sesiones centradas en la producción escrita a través de tareas significativas y contextualizadas. Los estudiantes trabajaron en pequeños grupos para crear proyectos escritos, como correos electrónicos, permitiéndoles aplicar estructuras del idioma en contextos reales de comunicación. Las actividades incluyeron revisión de tiempos gramaticales, ampliación de vocabulario y organización de ideas mediante conectores. Además, la retroalimentación constante del docente y entre pares permitió a los estudiantes reflexionar y mejorar su desempeño. Se concluye que el uso del ABP propició un aprendizaje activo, significativo y contextualizado, favoreciendo el desarrollo de habilidades de escritura en inglés. Asimismo, fomento la colaboración, el pensamiento crítico y la autonomía en el aula. Esta investigación demuestra la efectividad del ABP como estrategia metodológica en contextos educativos donde predomina la enseñanza tradicional.
Keywords: APRENDIZAJE BASADO EN PROYECTOS; HABILIDAD ESCRITA; METODOLOGIA ACTIVA; TRABAJO COLABORATIVO; ENSEÑANZA DEL INGLES